Potential effects of sea level rise on decomposition and nutrient release of dead fine roots in a Kandelia obovata forest. (5th May 2022) - Chen, Jiahui; Zhu, Heng; Huang, Yingying; Chen, Guangcheng; Ye, Yong
Abstract: Fine roots play an important role in the carbon dynamics and nutrient cycles of mangroves. Mangrove forests are threatened by sea level rise (SLR). Therefore, it is critical to understand how SLR affects dynamics of decomposition and nutrient release of dead fine roots to evaluate carbon dynamics and nutrient cycles of mangroves. Dynamics of decomposition and nutrient release of dead fine roots were compared among three sites under different intertidal elevations in a 11-year-old Kandelia obovata mangrove forest, representing tidal flooding situation of SLR values of 0, 40 and 80 cm, respectively. Mangroves at site SLR 80 cm had the highest dry weight loss of dead fine roots in the 10 and 30 cm soil layers. Mean rate of decomposition (MRD) at site SLR 80 cm was significantly higher than those at other sites, increasing by approximately 0.48 and 0.27 mg gDW −1 d −1 in the 10 cm and 30 cm soil layers due to SLR 80 cm, respectively. Site SLR 80 cm had significantly higher organic carbon (OC) losses of dead fine roots and OC loss percentages in the 10 cm soil layer than the other sites, while higher values were found at site SLR 40 cm in the 30 cm soil layer. Moreover, significantly higher nitrogen (N) losses of dead fine roots and N loss percentages were also found at site SLR 40 cm. These indicate that SLR will increase the rates of decomposition and release of nutrients of dead fine roots, which will accelerate carbon dynamics and nitrogen cycles of mangroves. Highlights: Potential sea level rise (SLR) increased decomposition of mangrove dead fine roots. Carbon loss in mangrove dead fine roots was high under high SLR. Potential SLR increased nitrogen release of mangrove dead fine roots.